Experiences of providing end-of-life care in adult intensive care units: a qualitative study - Dan-Dan Xu; Jin Li; Xin-Bo Ding; Jing Ma; Rui-Tong Hou; Na-Na Chen; Xiao-Lin Cheng; Fen Hu (BMC Nursing)
Abstract Objective To explore the perspectives and experiences of nurses providing end-of-life care in the intensive care units. Methods This study employed a descriptive phenomenological approach, conducting semi-structured interviews with 13 intensive care units’ nurses from November 2023 to February 2024. The interviews were audio-recorded, transcribed verbatim, and analyzed using Colaizzi analysis to categorize and organize the data. Results We categorized the findings into four themes: (1) Institutional constraints in end-of-life care, (2) Cultural-cognitive conflicts, (3) Communication breakdown and trust crisis, (4) Healing and resilience. Conclusion This study provides an in-depth analysis of the key factors influencing the implementation of end-of-life care in intensive care units within the Chinese cultural context, highlighting the multidimensional challenges encountered. By meticulously analyzing barriers and facilitators, the study offers insights for effective resource utilization (division of labor within the medical team, balancing the intensity of medical interventions with patients’ comfort needs) and targeted strategy development. Optimizing intensive care unit environments, enhancing cultural sensitivity education, promoting team collaboration, and providing emotional support for nurses are essential pathways to improving the effectiveness of end-of-life care in the intensive care units.